2010
DOI: 10.1007/s00468-010-0435-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth-unit structure in trees: effects of branch category and position on Nothofagus nervosa, N. obliqua and their hybrids (Nothofagaceae)

Abstract: In plants with rhythmic growth, a branch segment extended in one event is known as growth unit (GU). GU structure, resulting from the resources allocated to stem length, volume and mass, and to leaf area and mass, is relevant for understanding branch functioning in the context of plant development. This study compares GU structure between main branches and short branches positioned at low and high positions on nursery-grown trees of three closely related genetic entities: Nothofagus nervosa, N. obliqua and nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…Rosenthal et al (2002) reported intermediacy for SLA in three ancient hybrid species of Helianthus resulting from the hybridization between Helianthus annuus and Helianthus petiolaris . On the contrary, Puntieri and Ghirardi (2010) did not observe intermediacy of SLA between native hybrids of Nothofagus nervosa × Nothofagus obliqua and their parental species. In this study, S .…”
Section: Discussioncontrasting
confidence: 66%
“…Rosenthal et al (2002) reported intermediacy for SLA in three ancient hybrid species of Helianthus resulting from the hybridization between Helianthus annuus and Helianthus petiolaris . On the contrary, Puntieri and Ghirardi (2010) did not observe intermediacy of SLA between native hybrids of Nothofagus nervosa × Nothofagus obliqua and their parental species. In this study, S .…”
Section: Discussioncontrasting
confidence: 66%
“…The methodology employed here to determine the origin of trees, as differences or similarities in the growth pattern of natural trees, should be better studied and tested for future studies, including recent studies in tree architecture and growth-unit structure (e.g. GHIRARDI 2010;PUNTIERI et al, 2013).…”
Section: Comparisons and Relationships Between Dsi And Simentioning
confidence: 99%
“…Many biotic and abiotic factors, as suggested by previous studies, may potentially affect allometric relationships, including genetics, ontogeny, size, age, structure, site, climate, and their interactions [2,25,26,31,54,[61][62][63]. As shown in Figures 4 and 5, parameters of the allometric equations for different sites, age groups, and stand densities were heterogeneous at different scales, which implied that site, age, and stand density are attributed to the variation of internode allometry within and among Chinese pine trees.…”
Section: Discussionmentioning
confidence: 99%